Letter from Carl D. Duncan to Patricia Whiting, March 1, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan gives a long list of advice on how Whiting may keep herself out of danger when going on potentially dangerous dates with men.